Feasible techniques for valorisation of construction and demolition waste for concreting applications - H. M. S. C. H. Bandara; G. Thushanth; H. M. C. C. Somarathna; D. H. G. A. E. Jayasinghe; S. N. Raman (International Journal of Environmental Science and Technology, 2023)

Evolution of adverse drug reactions reporting systems: paper based to software based - M. T. Madhushika; T. P. Weerarathna; P. L. G. C. Liyanage; S. S. Jayasinghe (European Journal of Clinical Pharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Development of design guideline for the baseplate thickness of lattice towers - A. M. L. N. Gunathilaka; C. S. Lewangamage; M. T. R. Jayasinghe (Innovative Infrastructure Solutions, 2021)

Mercury and cadmium in swordfish and yellowfin tuna and health risk assessment for Sri Lankan consumers - B. K. K. K. Jinadasa; G. S. Chathurika; C. D. Jayaweera; G. D. T. M. Jayasinghe (Food Additives & Contaminants Part B-Surveillance, 2019)

Conversion between solid and beam element solutions of finite element method based on meta-modeling theory: development and application to a ramp tunnel structure - J. A. S. C. Jayasinghe; M. Hori; M. R. Riaz; M. L. L. Wijerathne; T. Ichimura (Earthquake Engineering and Engineering Vibration, 2017)

Screening of fungicides against Corynespora leaf fall disease of rubber under nursery conditions - T. H. P. S. Fernando; C. K. Jayasinghe; R. L. C. Wijesundera; D. Siriwardana (Journal of Plant Diseases and Protection, 2010)

Evaluation of screening methods against Corynespora leaf fall disease of rubber (Hevea brasiliensis) - T. H. P. S. Fernando; C. K. Jayasinghe; R. L. C. Wijesundera; W. P. K. Silva; E. A. D. N. Nishantha (Journal of Plant Diseases and Protection, 2010)

Variability of Hevea isolates of Corynespora cassiicola from Sri Lanka - T. H. P. S. Fernando; C. K. Jayasinghe; R. L. C. Wijesundera; D. Siriwardana (Journal of Plant Diseases and Protection, 2009)

Determining Tissue-Lead Levels in Large Game Mammals Harvested with Lead Bullets: Human Health Concerns - L. J. S. Tsuji; B. C. Wainman; R. K. Jayasinghe; E. P. VanSpronsen; E. N. Liberda (Bulletin of Environmental Contamination and Toxicology, 2009)

Lead Pellet Ingestion and Liver-Lead Concentrations in Upland Game Birds from Southern Ontario, Canada - N. Kreager; B. C. Wainman; R. K. Jayasinghe; L. J. S. Tsuji (Archives of Environmental Contamination and Toxicology, 2008)

Culture‐based fisheries in non‐perennial reservoirs in Sri Lanka: production and relative performance of stocked species - W. M. H. K. WIJENAYAKE; U. A. D. JAYASINGHE; U. S. AMARASINGHE; J. A. ATHULA; K. B. C. PUSHPALATHA; S. S. DE SILVA (Fisheries Management and Ecology, 2005)
In Sri Lanka, there is a great potential for the development of culture‐based fisheries because of the availability of around 12 000 non‐perennial reservoirs in the dry zone ( Catla catla Hamilton and rohu Labeo rohita Hamilton) and Chinese (bighead carp Aristichthys nobilis Richardson) major carps, common carp Cyprinus carpio L., genetically improved farmed tilapia (GIFT) strain of Nile tilapia, Oreochromis niloticus (L.) and post‐larvae of giant freshwater prawn, Macrobrachium rosenbergii De Man, at three different species combinations and overall stocking densities (SD) ranging from 218 to 3902 fingerlings ha −1 , during the 2002–2003 culture cycle. Of the 32 reservoirs stocked, reliable data on harvest were obtained from 25 reservoirs. Fish yield ranged from 53 to 1801 kg ha −1 and the yields of non‐perennial reservoirs in southern region were significantly ( P P P a and fish yield exhibited a positive second order relationship ( P P O. niloticus had the lowest specific growth rate among stocked species and freshwater prawn had a low return.

Tissue?Bismuth Levels of Game Birds Harvested with Bismuth Shotshell: Policy Implications - L. J. S. Tsuji; B. C. Wainman; R. K. Jayasinghe; J. D. Karagatzides; E. Van Spronsen; E. Nieboer (Bulletin of Environmental Contamination and Toxicology, 2004)